Political Economy of Reforms in MENA Region under Arab Spring Threats (2005 – 2013) - Al-Fawwaz, Abdulrahman (Dirasat: Human and Social Sciences, 2020)
The paper provides a comprehensive review on the political economic perspective towards the Arab spring. It gave a clear manifestation towards the threats faced after the Arab spring, which gave a rise to economic and political crisis within the Arab region and especially for MENA countries.The goal of this research is to scientifically contribute towards assessing the political and economic perspective from Arab spring era. The quantitative analysis has been conducted and variety of factors has been taken into consideration which affects the social, economic and political stability within MENA region. The quantitative method was selected and the major economic and political indicators were selected from the period of 2005 till 2013.The Study used t-test interpreted revealed that the Arab spring resulted in various other consequences such as the economic and political deteriorations. The study tried to answer the main question that "What is The Consequences and Outcome of Arab Spring"? in term of political changes, socio-economic development in the entire MENA region and to what extent it was achieved.The finding of study reveals that the Arab spring causes social, political and economic instability due to various complex factors. The result form the findings indicated that the Arab Spring has failed to create an outcome of optimistic changes; whereas it lead towards spread of religious radicalism, empower political Islamism and reduce state secularism. Therefore, this lead towards increase in civil wars, riots, intervention of neighbourhood, social militarization, Iranian hegemony, proxy wars, revival of terrorist cells and anarchized petrodollar. Hence, the findings from study collectively show the negative outcome of Arab spring on social, economic and political factors in the MENA region.